Ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, preparation method and application thereof, and lotion
By carrying VC-IP in soluble liquid crystal nanoparticles, the problems of low solubility and easy oxidation in water are solved, effective application and stability in water-based cosmetics are achieved, and skin feeling and biocompatibility are improved. sex.
Patent Information
- Application Number
- CN202310173488.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Ascorbic acid tetraisopalmitate (VC-IP) has low solubility in water and is easily oxidized, so it cannot be effectively applied in water-based cosmetics, resulting in greasy skin and poor absorption.
By carrying VC-IP in lyogenic liquid crystal nanoparticles, the lyogenic liquid crystal carrier and stabilizer aqueous solution composed of oil and grease and emulsifier is used to improve the solubility and stability of VC-IP in water, and form a lipid bilayer structure to Protect VC-IP, promote its absorption and controlled release.
It improves the solubility and stability of VC-IP in water, avoids oxidation, and achieves skin comfort and biocompatibility. It is suitable for the preparation of lotion, with good stability and industrial production applicability.
Smart Images

Figure CN116098832B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carrier systems in cosmetic preparation, and specifically relates to an ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, a preparation method and application thereof, and a lotion. Background Art
[0002] Ascorbyl Tetraisopalmitate (VC-IP) is a fat-soluble derivative of vitamin C. It is a colorless or light yellow liquid that is insoluble in water. Its structural formula is shown in Formula I. VC-IP has the effects of whitening and removing spots, promoting collagen growth, etc. It is often used as an antioxidant and is applied to beauty and skin care products.
[0003]
[0004] At present, when VC-IP is used in cosmetics, the products are mostly very oily products such as essences and creams, and the formula has disadvantages such as greasy skin feeling and poor absorption. VC-IP is a fat-soluble compound, which is difficult to dissolve in water and is easily oxidized in water. It cannot be converted into vitamin C to play an antioxidant role, so VC-IP cannot be directly applied to water-based products. Summary of the invention
[0005] The purpose of the present invention is to provide a dispersion of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles, a preparation method and application thereof, and a lotion in view of the existing problems. The dispersion of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles provided by the present invention increases the solubility of VC-IP in water, and at the same time improves the stability of VC-IP in aqueous solution, is not easily oxidized, and can be directly used in the preparation of lotion.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides an ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, which is prepared from raw materials comprising the following components: ascorbyl tetraisopalmitate, a lyotropic liquid crystal carrier and a stabilizer aqueous solution; the lyotropic liquid crystal carrier comprises oil and emulsifier; and the mass ratio of the ascorbyl tetraisopalmitate to the oil is 1 to 10:10.
[0008] Preferably, the oil comprises one or more of cetyl palmitate, glyceryl monolaurate, glyceryl behenate, glyceryl distearate, glyceryl monooleate, glyceryl monostearate, monoglyceryl succinate, caprylic decanoate, monoglyceryl oleate, propylene glycol monostearate, propylene glycol monooleate, propylene glycol monolaurate, sweet almond oil, hazelnut oil, soybean oil, olive oil and grape seed oil.
[0009] Preferably, the emulsifier includes one or more of decyl glucoside, lauryl glucoside, sucrose polystearate, cetyl palmitate, Tween 80 and coconut glucoside.
[0010] Preferably, the stabilizer in the aqueous stabilizer solution includes one or more of carbomer, sodium alginate, hyaluronic acid, magnesium stearate, xanthan gum and calcium stearate.
[0011] The present invention also provides a method for preparing the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical solution, comprising the following steps:
[0012] Mixing ascorbyl tetraisopalmitate, an emulsifier and oil to obtain an oil mixture;
[0013] emulsifying the oil mixture with a stabilizer aqueous solution to obtain nanoparticle colostrum;
[0014] The nanoparticle colostrum is dispersed to obtain the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion.
[0015] Preferably, the ratio of the oil mixture to the stabilizer aqueous solution is 1-10 g:50 mL, and the concentration of the stabilizer in the stabilizer aqueous solution is 0.1-3 wt %.
[0016] Preferably, the emulsification method includes shearing, and the shearing speed is 6000-12000 rpm and the time is 1-10 min.
[0017] Preferably, the dispersion method includes homogenization, the homogenization pressure is 400 to 1000 bar, and the number of times is 3 to 9 times.
[0018] The present invention also provides the use of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical solution in lotion.
[0019] The present invention also provides a lotion, which comprises the following components in mass fractions: 1-3% of ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, 80-93.37% of water, 0.03-1% of a chelating agent, 0.3-0.1% of an anti-inflammatory agent, 5-15% of a moisturizing agent and 0.3-1% of a preservative. The ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion is the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical solution or the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion obtained by the above preparation method.
[0020] The invention provides an ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, which is prepared from ascorbyl tetraisopalmitate, oil, emulsifier and stabilizer aqueous solution. The invention solves the problem of low solubility of VC-IP by encapsulating ascorbyl tetraisopalmitate (VC-IP) in lyotropic liquid crystal nanoparticles, wherein the lyotropic liquid crystal nanoparticles are composed of a lyotropic liquid crystal carrier and a stabilizer aqueous solution, and the lyotropic liquid crystal carrier is composed of oil and emulsifier, thereby improving the stability of VC-IP in aqueous solution and preventing oxidation. Meanwhile, the VC-IP lyotropic liquid crystal nanoparticles in the dispersion have a lipid double-layer structure, which is formed by self-assembly of an amphiphilic compound (oil), has hydrophobic tail ends facing each other and hydrophilic heads facing outwards, is similar to a cell membrane structure, and forms lyotropic liquid crystal nanoparticles, encapsulates VC-IP in a hydrophobic region of the lipid double-layer structure, can promote absorption of active ingredients, can control the release rate of VC-IP, and increase bioavailability.
[0021] The present invention also provides a method for preparing the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical scheme, which is simple and easy to implement. The ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticles have uniform particle sizes ranging from 80 to 200 nm and good dispersibility, and are suitable for industrial mass production.
[0022] The present invention also provides the use of the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical solution in lotion. The ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion of the present invention can be directly used as a cosmetic raw material to prepare lotion, which has a comfortable skin feel and good biocompatibility. After stability testing, no stratification or precipitation occurs, and the lotion has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 The present invention is a flow chart of the preparation process of the lotion;
[0025] Figure 2 This is a graph showing the chemical stability results of VC-IP lyotropic liquid crystal nanoparticles of Example 1;
[0026] Figure 3 : are electron microscope images of lyotropic liquid crystal nanoparticles, wherein a) is blank lyotropic liquid crystal nanoparticles, and b) is VC-IP lyotropic liquid crystal nanoparticles of Example 1;
[0027] Figure 4 The lotion freshly prepared in Example 1;
[0028] Figure 5 This is the lotion after being left at room temperature for 30 days;
[0029] Figure 6 This is the lotion after being placed in a 50℃ oven for 30 days;
[0030] Figure 7 This is the lotion after being stored at 4℃ for 30 days;
[0031] Figure 8 This is a lotion that has been through a freeze-thaw cycle. DETAILED DESCRIPTION
[0032] The invention provides an ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, which is prepared from raw materials comprising the following components: ascorbyl tetraisopalmitate, a lyotropic liquid crystal carrier and a stabilizer aqueous solution; the lyotropic liquid crystal carrier comprises oil and emulsifier; and the mass ratio of the ascorbyl tetraisopalmitate to the oil is 1 to 10:10.
[0033] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0034] In the present invention, the mass ratio of ascorbyl tetraisopalmitate to oil is preferably 5 to 10:10.
[0035] In the present invention, the oil preferably includes one or more of cetyl palmitate, glyceryl monolaurate, glyceryl behenate, glyceryl distearate, glyceryl monooleate, glyceryl monostearate, monoglyceryl succinate, caprylic decanoate, monoglyceryl oleate, propylene glycol monostearate, propylene glycol monooleate, propylene glycol monolaurate, sweet almond oil, hazelnut oil, soybean oil, olive oil and grape seed oil; more preferably, it is a mixture of glyceryl monostearate and hazelnut oil, a mixture of glyceryl monostearate and olive oil or a mixture of glyceryl monostearate and soybean oil, the mass ratio of glyceryl monostearate and hazelnut oil in the mixture of glyceryl monostearate and hazelnut oil is preferably 500:500, the mass ratio of glyceryl monostearate and olive oil in the mixture of glyceryl monostearate and olive oil is preferably 500:500, and the mass ratio of glyceryl monostearate and soybean oil in the mixture of glyceryl monostearate and soybean oil is preferably 500:500.
[0036] In the present invention, the emulsifier preferably includes one or more of decyl glucoside, lauryl glucoside, sucrose polystearate, cetyl palmitate, Tween 80 and coconut glucoside, more preferably lauryl glucoside, coconut glucoside or cetyl palmitate.
[0037] In the present invention, the mass ratio of the oil to the emulsifier is preferably 1000:150.
[0038] In the present invention, the stabilizer in the aqueous stabilizer solution preferably includes one or more of carbomer, sodium alginate, hyaluronic acid, magnesium stearate, xanthan gum and calcium stearate.
[0039] In the present invention, the particle size of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles in the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion is preferably 80 to 200 nm.
[0040] The present invention also provides a method for preparing the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical solution, comprising the following steps:
[0041] Mixing ascorbyl tetraisopalmitate, an emulsifier and oil to obtain an oil mixture;
[0042] emulsifying the oil mixture with a stabilizer aqueous solution to obtain nanoparticle colostrum;
[0043] The nanoparticle colostrum is dispersed to obtain the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion.
[0044] The invention mixes ascorbyl tetraisopalmitate, an emulsifier and oil to obtain an oil mixture.
[0045] In the present invention, the mass ratio of ascorbyl tetraisopalmitate to oil is preferably 1 to 10:10, more preferably 5 to 10:10.
[0046] In the present invention, the mixing temperature is preferably 40 to 70° C., more preferably 60° C., and the method for maintaining the mixing temperature is preferably a constant temperature water bath.
[0047] After obtaining the oil mixture, the present invention emulsifies the oil mixture with a stabilizer aqueous solution to obtain nanoparticle colostrum.
[0048] In the present invention, the oil mixture and the stabilizer aqueous solution are preferably first mixed before emulsification. During the first mixing, the temperature of the stabilizer aqueous solution is preferably the same as that of the oil mixture, and the first mixing temperature is preferably 40-70°C, more preferably 60°C.
[0049] In the present invention, the ratio of the oil mixture to the stabilizer aqueous solution is preferably 1-10 g:50 mL, more preferably 1.65-2.15 g:50 mL, and the concentration of the stabilizer in the stabilizer aqueous solution is preferably 0.1-3 wt %.
[0050] In the present invention, the emulsification method preferably includes shearing, the shearing speed is 6000-12000 rpm, more preferably 10000 rpm, and the time is preferably 1-10 min. The shearing rate of the present invention can quickly emulsify the oil phase and the water phase to form nanoparticle colostrum.
[0051] After obtaining the nanoparticle colostrum, the present invention disperses the nanoparticle colostrum to obtain the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion.
[0052] In the present invention, the dispersion method preferably includes homogenization, the homogenization pressure is preferably 400-1000 bar, more preferably 750 bar, the number of times is preferably 3-9 times, more preferably 6 times. The homogenization pressure and number of times described in the present invention can make the particle size of the nanoparticle colostrum more uniform and improve the dispersibility of the nanoparticles.
[0053] The preparation method of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion of the present invention is simple, and the particle size of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles obtained is uniform and has good dispersibility, and is suitable for mass production. The ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles obtained by the present invention have a lipid bilayer structure. According to the electron microscope image in the embodiment, the nanoparticles are all vesicle structures, and the long chain of VC-IP and the oil phase undergo self-assembly to promote the structure to change, and VC-IP is successfully loaded into the carrier.
[0054] The present invention also provides the use of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical solution in lotion.
[0055] The present invention also provides a lotion, which comprises the following components in mass fractions: 1-3% of ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, 80-93.37% of water, 0.03-1% of a chelating agent, 0.3-0.1% of an anti-inflammatory agent, 5-15% of a moisturizing agent and 0.3-1% of a preservative. The ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion is the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion described in the above technical solution.
[0056] In the present invention, the mass fraction of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion in the lotion is preferably 2-3%.
[0057] In the present invention, the mass fraction of water in the lotion is preferably 83-89%.
[0058] In the present invention, the mass fraction of the chelating agent in the lotion is preferably 0.05 to 0.07%.
[0059] In the present invention, the chelating agent preferably includes one or more of diethanolamine, sorbitol, EDTA-2Na, carboxymethyl chitosan and citric acid monohydrate.
[0060] In the present invention, the mass fraction of the anti-inflammatory agent in the lotion is preferably 0.3 to 0.5%.
[0061] In the present invention, the anti-inflammatory agent preferably includes one or more of dipotassium glycyrrhizinate, allantoin, aloe extract, calendula extract, curcumin and bisabolol.
[0062] In the present invention, the mass fraction of the moisturizing agent in the lotion is preferably 8-12%.
[0063] In the present invention, the moisturizer preferably includes one or more of glycerol, butylene glycol, polyethylene glycol, propylene glycol, xylitol, sodium lactate, sodium hyaluronate and panthenol, and is more preferably a mixture of glycerol and propylene glycol. The mass ratio of glycerol to propylene glycol in the mixture of glycerol and propylene glycol is preferably 3 to 7:5, and is more preferably 5:5.
[0064] In the present invention, the mass fraction of the preservative in the lotion is preferably 0.5%.
[0065] In the present invention, the preservative preferably includes one or more of phenoxyethanol, benzyl alcohol, propylparaben, pentylene glycol and hexylene glycol.
[0066] In the present invention, the lotion is preferably prepared by a method comprising the following steps:
[0067] The ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion and water are mixed for a second time to obtain a phase A;
[0068] The chelating agent, anti-inflammatory agent and moisturizing agent are mixed for the third time to obtain phase B;
[0069] After the phase A and the phase B are mixed for the fourth time, the phase A and the phase B are mixed for the fifth time with the preservative (phase C) to obtain the lotion.
[0070] The present invention has no special requirements for the second mixing and the third mixing methods, and methods well known to those skilled in the art may be used.
[0071] In the present invention, the volume ratio of phase A to phase B is preferably 6-10:1-4.
[0072] In the present invention, the mass ratio of phase A to phase B is preferably 88.95:10.55.
[0073] In the present invention, the fourth mixing and fifth mixing methods are preferably magnetic stirring, and the magnetic stirring is preferably carried out at room temperature. The rotation speed of the magnetic stirring is independently preferably 200-500 rpm, more preferably 400 rpm, and the time is independently preferably 10-60 min, more preferably 20-30 min.
[0074] After obtaining the lotion, the present invention preferably further comprises canning the finished product. The present invention has no special requirements on the method of canning the finished product, and a method well known to those skilled in the art can be used. The preparation process flow chart of the lotion of the present invention is as follows: Figure 1 shown.
[0075] The lotion of the present invention contains the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticles, and the water content of the VC-IP lyotropic liquid crystal nanoparticle dispersion is more than 85%. The lotion of the present invention has the effects of whitening and moisturizing.
[0076] To further illustrate the present invention, the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion provided by the present invention, its preparation method and application, and lotion are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0077] Example 1
[0078] 1. Take 500 mg of glyceryl monostearate, 500 mg of hazelnut oil and 150 mg of lauryl glucoside, mix them evenly in a 60°C water bath, then add 1000 mg of VC-IP and mix them with the oil in a 60°C water bath to obtain an oil mixture.
[0079] 2. The oil mixture was mixed with 50 mL of 0.1 wt% hyaluronic acid aqueous solution at 60°C, and high-speed sheared at 10,000 rpm for 1 min to obtain nanoparticle colostrum.
[0080] 3. Pour the nanoparticle colostrum into the material cup of the high-pressure homogenizer and circulate 6 times at a pressure of 750 bar to obtain VC-IP lyotropic liquid crystal nanoparticle dispersion.
[0081] 4. According to the lotion formula in Table 1, phase A and phase B were magnetically stirred at room temperature and 400 rpm for 30 minutes, and then phenoxyethanol (phase C) was added to the above system and magnetically stirred at room temperature for 30 minutes to mix the lotion evenly to obtain VC-IP lyotropic liquid crystal nanoparticle lotion.
[0082] Table 1 Formula of Example 1 Lotion
[0083]
[0084] Example 2
[0085] 1. Take 500g of glyceryl monostearate, 500g of olive oil and 150g of coconut glucoside, mix them evenly in a 60°C water bath, then add 500g of VC-IP and mix them with the oil in a 60°C water bath to obtain an oil mixture.
[0086] 2. The oil mixture was mixed with 50 L of 0.1 wt% sodium alginate aqueous solution (containing 50 g of sodium alginate) at the same temperature, and high-speed sheared at 10,000 rpm for 1 min to obtain nanoparticle colostrum.
[0087] The subsequent preparation method is the same as that in Example 1.
[0088] The formula and preparation method of VC-IP lyotropic liquid crystal nanoparticle lotion are the same as those in Example 1.
[0089] Example 3
[0090] 1. Take 500g of glyceryl monostearate, 500g of soybean oil and 150g of cetyl palmitate, mix them evenly in a 60℃ water bath, then add 1000g of VC-IP and mix them with the oil in a 60℃ water bath to obtain an oil mixture.
[0091] 2. The oil mixture was mixed with 50 L of 0.1 wt% magnesium stearate aqueous solution (containing 50 g of magnesium stearate) at the same temperature, and high-speed sheared at 10,000 rpm for 1 min to obtain nanoparticle colostrum.
[0092] The subsequent preparation method is the same as that in Example 1.
[0093] The formula and preparation method of VC-IP lyotropic liquid crystal nanoparticle lotion are the same as those in Example 1.
[0094] Test Example 1
[0095] Table 2 shows the particle sizes of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles in the VC-IP lyotropic liquid crystal nanoparticle dispersions of Examples 1 to 3.
[0096] Table 2 Particle size of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles in Examples 1 to 3
[0097] Example Example 1 Example 2 Example 3 Particle size (nm) 152.5 157.7 173.2
[0098] As shown in Table 2, the particle size of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles is in the range of 80 to 200 nm. The particle size of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles in the VC-IP lyotropic liquid crystal nanoparticle dispersion of Example 1 is the smallest, which is more suitable for the transdermal and absorption of nanoparticles.
[0099] Example 4
[0100] The raw material composition and preparation method of the VC-IP lyotropic liquid crystal nanoparticle dispersion are the same as those in Example 1.
[0101] The raw material composition of VC-IP lyotropic liquid crystal nanoparticle lotion is as follows:
[0102] Allantoin is used as an anti-inflammatory agent, and the amount added is 0.5% of the mass of the lotion; EDTA-2Na is used as a chelating agent, and the amount added is 0.05% of the mass of the lotion; glycerin and propylene glycol are used as moisturizers, and the amount added is 3% and 5% of the mass of the lotion respectively; phenoxyethanol is used as a preservative, and the amount added is 0.5% of the mass of the lotion, and the balance is water. The preparation method of the lotion is the same as that of Example 1.
[0103] Example 5
[0104] The raw material composition and preparation method of the VC-IP lyotropic liquid crystal nanoparticle dispersion are the same as those in Example 1.
[0105] The raw material composition of VC-IP lyotropic liquid crystal nanoparticle lotion is as follows:
[0106] Allantoin is used as an anti-inflammatory agent, and the amount added is 0.5% of the mass of the lotion; EDTA-2Na is used as a chelating agent, and the amount added is 0.05% of the mass of the lotion; glycerin and propylene glycol are used as moisturizers, and the amounts added are 7% and 5% of the mass of the lotion respectively; phenoxyethanol is used as a preservative, and the amount added is 0.5% of the mass of the lotion, and the balance is water. The preparation method of the lotion is the same as that of Example 1.
[0107] Test Example 2
[0108] Moisturizing rate test method: Take a 20-30cm long breathable tape and stick it on the glass plate, and weigh it as M0. Weigh 0.15g of lotion sample (M sample), evenly apply it on the breathable tape, place it in a constant temperature dryer for 24 hours, take it out and weigh it as M1, and calculate the moisturizing rate according to formula II. The results are shown in Table 3.
[0109]
[0110] Table 3 Changes in moisturizing rate of lotions in different embodiments
[0111] Example Example 1 Example 4 Example 5 Moisturizing rate (%) 14.93 12.32 10.59
[0112] Glycerin has good moisturizing properties because it contains multiple hydroxyl groups in its molecular structure and can absorb water twice its own volume. The final content of glycerin was screened based on the moisturizing rate. Without changing the content of other ingredients and only changing the glycerin content, the moisturizing rate of the lotion was the highest when the glycerin content in the lotion was 5%.
[0113] Test Example 3 Chemical Stability Determination
[0114] A VC-IP aqueous solution with a concentration of 100 ppm was prepared, and the VC-IP lyotropic liquid crystal nanoparticle dispersion prepared in Example 1 was diluted to form an aqueous solution containing VC-IP with a concentration of 100 ppm (VC-IP LCNPs). The sample was sealed in a transparent vial and placed at room temperature. The absorbance was measured using a UV-visible spectrophotometer on the first, seventh, fifteenth and thirtieth days to obtain the change in VC-IP content at different times. The difference in stability between VC-IP loaded in solute liquid crystal nanoparticles and pure VC-IP in aqueous solution was compared. The chemical stability results are shown in FIG. Figure 2 shown.
[0115] Depend on Figure 2 It can be seen that VC-IP has low solubility in water and will be rapidly oxidized within 4 hours, resulting in a rapid decrease in the VC-IP content. The solubility and stability of VC-IP in water are greatly improved after being encapsulated by lyotropic liquid crystal nanoparticles, indicating that loading VC-IP on lyotropic liquid crystal nanoparticles has a good protective effect on VC-IP, increasing its stability in water, and significantly improving its utilization and storage rates.
[0116] Test Example 4 Physical Stability Determination
[0117] 1. Stability of VC-IP lyotropic liquid crystal nanoparticles
[0118] 1) Centrifugal stability
[0119] Take 2 mL of the freshly prepared VC-IP lyotropic liquid crystal nanoparticle dispersion in Example 1, place it in a 10 mL centrifuge tube, centrifuge it at 25°C for 0, 10, 20, 30, and 40 min, respectively, and the centrifugal speed is 4000 rpm. Observe the state of the sample after centrifugation. If no stratification occurs, measure its average particle size and PDI, and calculate the centrifugal stability parameter K E , evaluate its centrifugal stability, the calculation formula is shown in Formula III, and the centrifugal stability results are shown in Table 4.
[0120]
[0121] Where R0 is the particle size before centrifugation, and R is the particle size after centrifugation.
[0122] Table 4 Centrifugal stability results
[0123] Time (min) Particle size (nm) PDI <![CDATA[K E (%)]]> state 0 126.0 0.16 --- Unstratified 10 126.7 0.15 0.58 Unstratified 20 129.0 0.14 2.41 Unstratified 30 127.0 0.13 0.83 Unstratified 40 125.1 0.13 0.65 Unstratified
[0124] VC-IP lyotropic liquid crystal nanoparticles showed no stratification or precipitation at the same speed and different centrifugation times, and the particle size and PDI did not change significantly. The centrifugal stability parameter K EMaintaining below 5%, it indicates that the VC-IP lyotropic liquid crystal nanoparticles in the VC-IP lyotropic liquid crystal nanoparticle dispersion of the present invention have good stability.
[0125] 2) Freeze-thaw stability
[0126] The VC-IP lyotropic liquid crystal nanoparticle dispersion of Example 1 was placed at -20°C, and samples were taken out at intervals of 0, 0.5, 1, 1.5, and 2 h, respectively, and thawed at room temperature. The average particle size and PDI value of the samples frozen for different times after thawing were tested. The results are shown in Table 5.
[0127] Table 5 Freeze-thaw stability results
[0128] Time (h) Particle size (nm) PDI 0 148.6 0.2 0.5 147.5 0.2 1 145.0 0.2 1.5 144.1 0.2 2 142.2 0.2
[0129] As shown in Table 5, at different freeze-thaw times, the particle size and PDI of VC-IP lyotropic liquid crystal nanoparticles did not change significantly, indicating that VC-IP lyotropic liquid crystal nanoparticles can be stored for a short period of time at a low temperature of -20°C without affecting the stability of the sample. Combined with the centrifugal stability results, it can be seen that VC-IP lyotropic liquid crystal nanoparticles have good stability and can be added to cosmetics as a cosmetic raw material.
[0130] 3) Cryo-TEM
[0131] The VC-IP lyotropic liquid crystal nanoparticle dispersion of Example 1 was dropped onto a copper mesh, which was quickly immersed in liquid ethane at -180°C to vitrify the mesh, and then stored in liquid nitrogen. The sample was observed and photographed using a 200KV transmission electron microscope.
[0132] The electron microscope image of the blank lyotropic liquid crystal nanoparticle carrier shows that there are nanoparticles with obvious "cauliflower-like" structure, such as Figure 3 As shown in a), it is a classic morphology of sponge phase, and there are some smaller vesicle structures scattered around, indicating that the blank carrier is a system where sponge phase and vesicles coexist. In the cryo-EM image of VC-IP lyotropic liquid crystal nanoparticles, the nanoparticles are all vesicle structures, such as Figure 3 As shown in b), it is considered that the long chain of VC-IP self-assembles with the oil phase to cause the structural change, which also proves that VC-IP has been successfully loaded into the carrier.
[0133] 2. Stability of VC-IP lyotropic liquid crystal nanoparticle lotion
[0134] 1) Storage stability
[0135] The lotion prepared in Example 1 was placed in a room temperature, a 50° C. oven high temperature environment, and a 4° C. low temperature environment, and after 30 days, the samples were observed for changes in appearance and for stratification.
[0136] 2) Freeze-thaw cycle stability
[0137] The lotion prepared in Example 1 was placed in a 50°C oven, taken out after 12 hours and placed in a 4°C refrigerator, and then placed in a 50°C oven after another 12 hours. After repeating this process three times, the sample was returned to room temperature and observed to see if it was separated into layers.
[0138] Figure 4 is the freshly prepared lotion in Example 1, Figure 5 This is the lotion after being left at room temperature for 30 days. Figure 6 This is the lotion after being placed in a 50℃ oven for 30 days. Figure 7 This is the lotion that has been stored at 4℃ for 30 days. Figure 8 It is a lotion after freeze-thaw cycle. Figures 4 to 8 It can be seen that after the storage stability test under different conditions, the lotion still has good uniformity and no stratification or precipitation occurs, indicating that the lotion has good stability.
[0139] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creativity, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A lyotropic liquid crystal nanoparticle dispersion of ascorbyl tetraisopalmitate, characterized in that: The preparation method of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion comprises the following steps: Take 500 mg of glyceryl monostearate, 500 mg of hazelnut oil and 150 mg of lauryl glucoside, mix them evenly in a 60°C water bath, then add 1000 mg of ascorbyl tetraisopalmitate, and mix them with the oil in a 60°C water bath to obtain an oil mixture; The oil mixture was mixed with 50 mL of a 0.1 wt% hyaluronic acid aqueous solution at 60° C., and high-speed sheared at 10,000 rpm for 1 min to obtain nanoparticle colostrum; The nanoparticle colostrum was poured into a material cup of a high-pressure homogenizer and circulated for 6 times at a pressure of 750 bar to obtain a dispersion of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles.
2. The method for preparing the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion according to claim 1, characterized in that: The following steps are involved: Take 500 mg of glyceryl monostearate, 500 mg of hazelnut oil and 150 mg of lauryl glucoside, mix them evenly in a 60°C water bath, then add 1000 mg of ascorbyl tetraisopalmitate, and mix them with the oil in a 60°C water bath to obtain an oil mixture; The oil mixture was mixed with 50 mL of a 0.1 wt% hyaluronic acid aqueous solution at 60° C., and high-speed sheared at 10,000 rpm for 1 min to obtain nanoparticle colostrum; The nanoparticle colostrum was poured into a material cup of a high-pressure homogenizer and circulated for 6 times at a pressure of 750 bar to obtain a dispersion of ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticles.
3. Use of the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion according to claim 1 or the ascorbyl tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion obtained by the preparation method according to claim 2 in preparing lotion.
4. A lotion, characterized in that: The invention comprises the following components in mass fractions: 1-3% of ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion, 80-93.37% of water, 0.03-1% of chelating agent, 0.3-0.1% of anti-inflammatory agent, 5-15% of moisturizing agent and 0.3-1% of preservative. The ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion is the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion according to claim 1 or the ascorbic acid tetraisopalmitate lyotropic liquid crystal nanoparticle dispersion obtained by the preparation method according to claim 2.
Citation Information
Patent Citations
Whitening liquid crystal composition as well as preparation method and application thereof
CN108451837A
